Analysis of Factors Affecting Waiting Time for Results of Clinical Laboratory Examinations at Medan Haji General Hospital - Pande Luthfhy Rahayu; Thomson Nadapdap; Deli Theo (Newinera Publisher, 2021)
The purpose of this study was to analyze the factors that affect the waiting time for clinical laboratory examinations at RSU Haji Medan in 2021. This study is a mixed method. Using a total sampling of 17 people, namely all laboratory workers, the main informants in this study were clinical pathology doctors, room coordinators, clinical laboratory analysts at Haji Medan General Hospital (RSU) totaling 3 people and patients totaling 3 people. 1 additional informant, namely the Management section at RSU Haji Medan. The quantitative results are that there is a relationship between the qualifications of laboratory personnel having a value of p = 0.000, at the facility p = 0.044, there is no relationship between the transportation of specimens, the value of p = 0.099, there is a relationship between pre-analytical, analytical and pre-analytical problems. post analytic p value = 0.022, there is no electrical stability relationship p value = 0.235. Based on the results of research according to information and informants about the qualifications of officers running smoothly. have to send the sample to a private laboratory. Based on these results, it was concluded that the waiting time for laboratory results at RSU Haji has reached the standard that is in accordance with the minimum service standards at the Haji General Hospital in Medan City.